PLANTING CHARACTER VALUES IN THE COMMUNITY OF NAGARI ABAI SIAT, DHARMASRAYA REGENCY THROUGH THE NDUK TUO TRADITION - Naufal Raid; Inge Angelia (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
The occurrence of moral degradation among the people, such as individualism, intolerance, bullying, requires the cultivation of character values ​​in society. The cultivation of these character values ​​is not only carried out in formal schools, but can also be carried out in the community, for example through existing traditions in the community, for example the nduk tuo tradition in Nagari Abai Siat. The research method used is qualitative, the data collection tools used are observation, interviews and documentation. Data analysis techniques use the Milles and Huberman models. The results of the research are the nduk tuo tradition which is still maintained by the people of Nagari Abai Siat for generations, this nduk tuo tradition is an activity to raise funds for the people who will carry out the marriage. The values ​​of character education contained in the nduk tuo tradition are (1) creativity, (2) social care, (3) a sense of togetherness and solidarity, (4) responsibility